OPTIMALISASI PENJUALAN KAIN ENDEK DENGAN METODE KARUSH-KUHN-TUCKER (KKT) - PUTRA, I GEDE ARIS JANOVA; ASIH, NI MADE; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 4 No 4 (2015), 2015)
This study is conducted to determine the optimal sales value of endek mastuli, endek rangrang, endek  saraswati, endek gradasi, and endek alam in Novala Busana Shop and Trans Collection Shop in order to reache maximum advantage by using Karush-Kuhn-Tucker (KKT) method. Karush-Khun-Tucker method  can be used to find the optimum solution of the function regardless of whether linear or nonlinear. In the  workmanship is KKT method essentially involves the same steps as Lagrange method, from a Lagrangean  to be able to calculate the critical points, finding all solutions , and calculate of the value . In  this study, most of quarterly show that which must be sold are kind of endek mastuli in reaching the  maximum benefit. For other kinds of endek is constantly provided but it is not as much as before.  Suggested to the next research could involve more variated variable with more interesting cases
Keywords: Karush-Khun-Tucker (KKT) method; Lagrangean; Optimization; Constraint; Endek